Analisis Kemudahan Penggunaan Fitur Customer on Boarding pada Aplikasi Muamalat DIN di PT Bank Muamalat Cabang Pekanbaru - Isyraq, Anisah (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
This study aims to analyze the ease of use of the Customer on Boarding (COB) feature in the Muamalat DIN application at PT Bank Muamalat Branch Pekanbaru. The research used a descriptive qualitative approach, with data collection techniques consisting of participatory observation and document review. Primary data were obtained through direct assistance to prospective customers opening accounts online, while secondary data came from internal bank documents and relevant literature. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the COB feature provides significant convenience to prospective customers, including independent account registration without visiting the branch, a fast procedure, secure digital verification, flexible time and location, and accounts that are ready to use immediately. However, several challenges remain, such as dependence on a stable internet connection, delays in receiving OTP codes, and the unavailability of services for foreign nationals. Data validity was ensured through source triangulation, while research ethics were upheld through participant consent and the protection of personal data.